2009
DOI: 10.1002/ajmg.a.32814
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and 244k array‐CGH characterization of chromosome 13q deletions: An update of the phenotypic map of 13q21.1‐qter

Abstract: Partial deletions of the long arm of chromosome 13 lead to variable phenotypes dependant on the size and position of the deleted region. In order to update the phenotypic map of chromosome 13q21.1-qter deletions, we applied 244k Agilent oligonucleotide-based array-CGH to determine the exact breakpoints in 14 patients with partial deletions of this region. Subsequently, we linked the genotype to the patient's phenotype. Using this approach, we were able to refine the smallest deletion region linked to short sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
94
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 32 publications
10
94
1
Order By: Relevance
“…A good candidate gene is PCDH9 that encodes for a cadherin-related neuronal receptor that localizes to synaptic junctions and has a putative role in specific neuronal connections and signal transduction. 31 Of note, all deletions found in our cohort are centromeric to 13q33.3q34, a region that was reported to be critical for microcephaly by Kirchhoff et al 30 Interestingly, a few patients in this cohort and in previous reports showed macrocephaly. 8,9 However, the pattern of deleted regions was the same as that in patients with normocephaly.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A good candidate gene is PCDH9 that encodes for a cadherin-related neuronal receptor that localizes to synaptic junctions and has a putative role in specific neuronal connections and signal transduction. 31 Of note, all deletions found in our cohort are centromeric to 13q33.3q34, a region that was reported to be critical for microcephaly by Kirchhoff et al 30 Interestingly, a few patients in this cohort and in previous reports showed macrocephaly. 8,9 However, the pattern of deleted regions was the same as that in patients with normocephaly.…”
Section: Discussionsupporting
confidence: 61%
“…[27][28][29] Micrognathia was reported as a common dysmorphic feature in patients with 13q deletions and was associated with loss of the region 13q21.33q31.1. 30 Additional mild anomalies of the feet were found in 17 patients. Caselli et al 2007 also reported on toe crowding and a short V toe in 2/3 patients with an interstitial 13q deletion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Partial deletions in chromosome 13q lead to variable phenotypes based on the size and position of the deleted region [5]. While distal deletions are closely associated with severe phenotypes, proximal deletions tend to cause fewer major anomalies, with the exception of retinoblastoma [6].…”
Section: Discussionmentioning
confidence: 99%
“…Lele et al (1963) first described a partial deletion of 13q in retinoblastoma patients who also displayed intellectual disabilities and global developmental delays . The 13q deletion syndrome leads to phenotypes that include short stature, microcephaly, cerebral cortical malformations, Dandy-Walker malformation (DWM), corpus callosum agenesis, meningocele/encephalocele, neural tube defects, micro-/anophthalmia, cleft lip/palate, lung hypoplasia, heart defects, genital anomalies, and hand abnormalities (Kirchhoff et al, 2009;Chen et al, 2013;Valdes-Miranda et al, 2014). In this study, we used 3 laboratory methodologies to report the first postnatal diagnosis in Central Brazil of a child with cytogenetic abnormalities involving chromosome 13.…”
Section: Introductionmentioning
confidence: 99%